Study of gastric secretion in liver cirrhosis - García Lucero, Orlando (1967)
Gastric secretion was studied with high histamine stimulation in a group of 31 patients with liver cirrhosis , comparing the results with the values ​​found in a group of normal people called controls and another group with duodenal ulcer. Patients with liver cirrhosis secrete very little hydrochloric acid, both in basal conditions and after a high histamine stimulation , being 1.77 ± 1.66 mEq DAB total HCl, and 7.13 ± 5.35 mEq DAM . This gastric hyposecretion not depend on the degree of hepatic decompensation. It is possible that a small number of parietal cells is due by chronic atrophic gastritis subsequent to the toxic effects of alcohol, malnutrition or some other factor . It would be interesting to study gastric secretion in alcoholics without cirrhosis and without cirrhosis in malnourished to explain this finding. In 24 cirrhotic patients undergoing upper gastrointestinal study logical within 20 % with duodenal ulcer ! , Higher incidence than that for the general population ( 10) was found. Gastric secretion in cirrhotic patients with duodenal ulcer was higher than in non-ulcer , and secretion statistically similar to controls and duodenal ulcer . The DAB was 9.51 ± 6.17 and the DAM : 29.23 ± 4.69 mEq total HCl. It is necessary to expand the study with larger number of cases pear more definitive conclusions.